Technological systems and intersectoral innovation flows - Leoncini, Riccardo, 1959-; Montresor, Sandro, 1968- (Cheltenham, UK ; Northampton, MA : E. Elgar, 2003)
This book examines long-run technological change and the complex set of interrelated phenomena which can be grouped under the heading of 'innovative processes'. The author refer to a broad notion of the technological system and propose an original methodology to ensure consistent empirical analysis.
Includes bibliographical references (p. 201-215) and indexes.
rpm 31/05/13
Loans
Keywords: Technological innovations